2014
DOI: 10.1155/2014/150298
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Polyamide-12 versus PMMA Denture Base Material

Abstract: Objectives. Polyamide-12 (PA) is a flexible material suited for denture bases and clasping. This study investigated its potential aging effects with a focus on surface roughness, color stability, and elasticity. Methods. PA specimens (Valplast) of 40 × 10 × 2 mm and equally measuring PMMA specimens (Palapress) as control were fabricated. Color changes after storage in air, water, coffee, and red wine (n = 10) were measured using the CIE L*a*b* color specification. Elasticity after thermocycling (1000, 3000, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
47
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 27 publications
9
47
1
3
Order By: Relevance
“…They are considered to be superior to conventional RPDs with metal clasps in terms of esthetics; however, the use of NMCDs made from thermoplastics, especially polyamide, may seriously affect some tissues because of the low rigidity of thermoplastics. Several types of polyamide are commercially available 4,18) . Polyamides are semicrystalline polymers whose repeating units are characterized by the amide group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are considered to be superior to conventional RPDs with metal clasps in terms of esthetics; however, the use of NMCDs made from thermoplastics, especially polyamide, may seriously affect some tissues because of the low rigidity of thermoplastics. Several types of polyamide are commercially available 4,18) . Polyamides are semicrystalline polymers whose repeating units are characterized by the amide group.…”
Section: Discussionmentioning
confidence: 99%
“…Removable partial dentures (RPDs) using resin-clasp retentive parts are defined as non-metal clasp dentures (NMCDs), and are often much more esthetically pleasing than conventional RPDs with metal clasps 2) . Generally, thermoplastic resins such as polyamide, polyester and polycarbonate have been used as NMCDs that can be injection-molded in one piece including clasps, minor and major connectors, and denture bases [2][3][4] . Several types of polyamides are most commonly used, having the longest history among the thermoplastic resins used for NMCDs 2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface roughness play a major role in microbiological attachment, more rougher the surface more the candidal count. 7 Surface roughness and surface free energy (SFE) may contribute to the positively correlated rate of microbial colonization and plaque maturation on surfaces. 8 The result of the microbiological study have showed that the finishing and polishing technique that show lower surface roughness value have less number of Candidal cells attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Micro cracks produced by direct contact with acidic fluids in a certain concentration and intensity level. 5,6 Surface roughness is a condition where a surface condition of one object is wavy and irregular. 7 The condition of the surface of heat cured acrylic resin denture base material inside the oral cavity will affect plaque buildup that will increase the amount of Candida albicans colony that can cause denture stomatitis.…”
Section: Introductionmentioning
confidence: 99%